2021
DOI: 10.3390/cancers13092203
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Management of Complex Hepatectomy for Colorectal Liver Metastases: The Alliance between the Surgeon and the Anesthetist

Abstract: Hepatic resection has been widely accepted as the first choice for the treatment of colorectal metastases. Liver surgery has been recognized as a major abdominal procedure; it exposes patients to a high risk of perioperative adverse events. Decision sharing and the multimodal approach to the patients’ management are the two key items for a safe outcome, even in such a high-risk surgery. This review aims at addressing the main perioperative issues (preoperative evaluation; general anesthesia and intraoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 115 publications
(152 reference statements)
0
15
0
Order By: Relevance
“…are available for preoperative volumetric evaluation. In addition to providing volumetric data, newer software-based imaging devices can produce a three-dimensional reconstruction of the hepatic anatomy, tumour extent and its relation to vital structures [4 ▪▪ ,27,28 ▪▪ ]. It should nonetheless be highlighted that despite being a strong predictor of postoperative outcomes, liver volume is basically a surrogate marker for function.…”
Section: Quantitative Assessment Of the Livermentioning
confidence: 99%
See 3 more Smart Citations
“…are available for preoperative volumetric evaluation. In addition to providing volumetric data, newer software-based imaging devices can produce a three-dimensional reconstruction of the hepatic anatomy, tumour extent and its relation to vital structures [4 ▪▪ ,27,28 ▪▪ ]. It should nonetheless be highlighted that despite being a strong predictor of postoperative outcomes, liver volume is basically a surrogate marker for function.…”
Section: Quantitative Assessment Of the Livermentioning
confidence: 99%
“…Perioperative blood transfusions are associated with poor long-term survival in liver cancers and measures to reduce blood loss are always sought [4 ▪▪ ,42,43]. RCTs have shown that intraoperative terlipressin reduced portal pressures and blood loss without any adverse effects.…”
Section: Perioperative Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The normal range of SVV under controlled ventilation is less than 10-13%. During the resection phase, a SVV of 10-15% can be accepted, while a SVV ≤10% after liver resection represents the target [18,19].…”
Section: Vascular and Bleeding Control And Hemodynamic Monitoringmentioning
confidence: 99%